A Formalist Stylistic Reading of a Filipino Poem: Using Blake’s Syntactic Approach - Tan de Ramos, Jennifer (International Journal of Language and Literary Studies, 2025)
Literature, particularly poetry, is a rich area to investigate in terms of its relations to linguistic structures. In this study, a poem written by a Filipino poet is subjected to a close textual analysis using Blake’s (1990) syntax. The study employs the formalist stylistic approach (Jakobson, 1991) to conduct a close textual analysis of the sentence structure in Emmanuel Torres’ poem It is Difficult to Speak of Saints (1972). One primary observation drawn from examining the poem is its deviation from conventional poetic norms, such as its use of unusual collocations, apposition, and irregular rhyming patterns. Further analysis of the sentence structure through Blake’s (1990) syntactic framework seeks to unravel the predominant patterns in the poem and their effects on the reader. Blake’s syntax categorizes sentence elements into five components: subject, predicator, object, complement, and adjunct, which were examined to understand their roles and their effects on the readers. In addition, noun groups and verb groups were analyzed to uncover their structural nuances. Upon analysis, the poem, structured as free verse with four stanzas, reveals a diminishing rhyming pattern, reflecting the persona’s fading faith. Ultimately, analysis using Blake’s syntax reveals how sentence structures and stylistic choices contribute to the poem’s thematic depth and emotional resonance, ultimately guiding the reader to grasp its underlying message.